A novel fault location algorithm for mixed overhead‐cable transmission system using unsynchronized current data. Issue 9 (3rd June 2019) - Ding, Jiali; Wang, Xin; Zheng, Yihui; Li, Lixue
Abstract : The characteristic impedance value of the overhead line is different from that of the underground cable. Existing traveling wave‐based fault location methods for mixed power transmission systems have setbacks including location error caused by wave velocity and difficulty in detecting wave arrival time. In order to solve these problems, the increase of available information from different locations by installing wire‐based sensors along the power line is a feasible solution. In this paper, a traveling wave‐based fault location system, which is based on the current data measured at the midpoint of the overhead line and the joint point, is introduced. The data at these two locations are measured by the wire‐based current sensor we designed. The whole transmission line system is divided by these two sensors into three segments. The first step of this proposed method is to record the postfault current data at the two measuring devices. Second, by comparing the amplitudes and polarities of the current at these two measurement points, the faulty segment can be identified. Finally, postfault wave propagation paths are ascertained; the accurate velocity values of the waves in the overhead line and underground cable are obtained; and then, the fault point is located without the need of time synchronization. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.